Sedative Effect of Ketamin-Midazolam Administered at Acupoint GV20 Compared to Intramuscular Route in Blue-Fronted Amazon (Amazona aestiva): a Pilot Study - Aricia Noelli Brega Monteiro; Bruno Simões Sérgio Petri; Haroldo Furuya; Liliane Milanelo; Márcia Valéria Rizzo Scognamillo; Ayne Murata Hayashi (Medical Association of Pharmacopuncture Institute, 2022)
Background : The growth of exotic pet medicine is leading to fast developments in clinical investigations on birds. Acupuncture, specifically pharmacopuncture, offers safe chemical restraint options. Objectives: To investigate pharmacopuncture at acupoint GV20 in blue-fronted Amazon parrots (Amazona aestiva) using ketamine and midazolam. Methods : Sixteen healthy birds were distributed into four groups (C: intramuscular control; 1/2 C: 1/2 dose intramuscular control; 1/2 GV20: 1/2 dose at acupoint GV20; 1/5 GV20: 1/5 dose at acupoint GV20). Degree of sedation, latency, recuperation time, heart and respiratory rate, and body temperature were measured. Quantitative data were analyzed by a Student's t-test. Results : The C, 1/2 C, and 1/2 GV20 groups showed the same degree of sedation. The 1/2 GV20 group showed longer latency times (6 ± 2.1) than the 1/2 C (2.5 ± 0.5) group. Sedation time did not differ between the C (28 ± 9.8), 1/2 C (30.5 ± 8.6), and 1/2 GV20 (41 ± 22.24) groups. The 1/2 GV20 group recuperated faster (13.7 ± 3.7) than the C group (64.2 ± 3.5). The C and 1/2 C groups showed tremors and slow and unstable recovery. Two animals in the C group showed mild hypothermia (38°C). Conclusion : The use of 1/2 GV20 was effective and safe to sedate blue-fronted Amazon parrots without side effects, providing easy, stable, and fast recovery. The use of 1/5 GV20 had a shorter sedation time. These findings show that the combination of acupuncture and drugs provides new possibilities for efficient anesthetic protocols with fewer side effects in birds.